Enseñanza y aprendizaje de la estadística en estudiantes de grado noveno: implementación de una unidad didáctica basada en la educación matemática realista (2024)
The general objective of this work is to evaluate the effectiveness of teaching material for the development and strengthening of statistical and random thinking and data systems, through a Realistic Mathematics Education (RME) approach in ninth grade students at an official school of the city of Bogotá. The foundation was carried out within the theoretical framework of the EMR and the basic concepts of random thinking for ninth grade, such as: population, sample, types of variables, frequency tables, statistical graphs, and measures of central tendency.